Mapping Research Systems in Kenya, Tanzania, and Rwanda and their Relation with the Sustainable Development Goals (2022)
ABSTRACT: Chapter 9 analyses the complex interactions between social demands and scientific knowledge production. The chapter uses knowledge mapping techniques to understand how research priorities in Kenya, Rwanda, and Tanzania are aligned with the main socio-economic challenges expressed in the industry standards, and the Sustainable Development Goals (SDGS).